National strategies to fight homelessness and housing exclusion - Koutsampelas, Christos; Andreou, Sofia N.; Tsolaki, Evi (My University, 2019)
Homelessness and housing exclusion (HHE) are infrequent in Cyprus. The rarity of the problem is the main reason explaining why HHE has never been prioritised in the social policy agenda. As a result, HHE is not systematically documented and monitored, with very few and scattered data regarding the number and profile of homeless persons. The lack of data drastically impedes the analysis of the problem and the formulation of appropriate policies. The policy framework is also characterised by an absence of a national strategy that could effectively coordinate fragmented policies and the regional initiatives which sporadically surface (as the problem of HHE is indeed rare but not non-existent). The regulatory framework is also insufficient, as there is no official national definition of homelessness in the legislation or in any official document. The ETHOS1 typology has not been formally adopted, nor has any version of it been applied at the national or the regional level. Finally, there are no monitoring mechanisms available. Suffice to say that these operational deficiencies severely limit the visibility of the problem, reduce public awareness and hinder the effective implementation of policies. Recent evidence on HHE indicates an escalation of the problem, with the number of homeless persons increasing in some areas between 2015 and 2017, possibly due to the recent steep increases in residential prices and rents. The lack of information does not allow the robustness of this trend to be verified or reliable conclusions to be drawn about the profile of homeless persons. However, the government has responded positively by announcing an increase in the level of the housing allowance. HHE in Cyprus is mainly combated through general poverty-reduction policies and, in particular, through the guaranteed minimum income (GMI). Under this scheme, recipients may receive a housing allowance. Eligibility covers not only renters but also households who face difficulties in paying off their mortgage. Additionally, a new scheme, called Estia, is currently being implemented, aimed primarily at protecting the primary residence of debt-overburdened households. Although these policies serve wider goals, they are useful in limiting the incidence of HHE too. However, support services to persons at risk of HHE is a policy area that is not adequately developed, and is characterised by fragmentation. There are several shelters providing temporary and/or emergency accommodation to vulnerable groups. Two shelters are currently operating, one in Nicosia and one in Paphos, providing, among other services, accommodation to victims of domestic violence; and another state shelter for women will start to operate soon. There is also a shelter for victims of human trafficking. Furthermore, Social Welfare Services (SWS) may offer temporary/emergency accommodation to homeless persons until a better solution is provided. Useful initiatives are also planned at the regional level. Currently, the Council of Community Volunteerism of Germasogeia in the district of Limassol is planning the implementation of one of the first temporary accommodation centres for homeless people in Cyprus. The homeless centre ‘Solidarity’ will provide temporary accommodation to persons at risk of HHE. The basic purpose will be to provide first-aid relief services and psycho-social support to people without secure housing who are living on the streets, in abandoned buildings or in improvised shelters. In the second stage, the centre will target their reintegration into society. In addition, the Municipality of Limassol is planning to operate a service centre for supporting vulnerable adults, aimed at providing first-aid and social support services to adults at risk of HHE. Overall, the policy framework in Cyprus is characterised by several weaknesses such as: lack of information and monitoring mechanisms; lack of a national strategy, or at least a strategic approach to fighting HHE; and inadequate welfare benefits (i.e. low level of housing allowance). However, there is much scope for improvement, with the first necessary steps being the design of a national strategy, the collection and dissemination of information on HHE, and the implementation of activities for raising social awareness.